Detecting deception during a structured interview. - Leritz, Lyle E. (My University, 2004)
Deception is a part of everyday life for many people. Given this reality, how can employers be certain employees are being relatively honest during interviews? Can an interviewer be trained to detect deception while conducting an interview? The purpose of this research was to determine if an interviewer could be trained to detect deception while conducting an interview. To address this, participants were given one of three levels of training, including structured interview training, deception detection training, and probe question training. Each level of training included the previous level(s) of training. Following training, participants interviewed another person using the criteria checklist from training. After the interview, participants completed a questionnaire where they rated, among other things, honesty and deceptiveness. Additionally, participants reviewed the interview on videotape, again using the criteria checklist and completing a second questionnaire. Results indicated that training improved performance relative to no training in terms of criteria application. However, training beyond the criteria (e.g., probe training) reduced the ability to use the criteria checklist, but did not reduce accuracy in applying the criteria. Additionally, training did not influence the overall judgments. Finally, there were no differences between the interview and the video review in terms of judgments and criteria application.
Keywords: Psychology, Industrial.; Deception.